The production materials analysis of popular novel in Meniti Rindu - Mohamed Nazreen Shahul Hamid; Phat Awang Deng; Rohaya Md Ali (Penerbit Universiti Kebangsaan Malaysia, 2024)
Generally, it is known that the presence of popular novels in the local literary scene is not a new phenomenon. However, the enthusiasm for this genre still persists to this day and continues to dominate the local novel sales market. Nevertheless, popular novels have never been free from criticism due to their tendency to adhere to the same writing formula. Furthermore, they are often accused of placing women in improper positions. Nonetheless, Affifudin Omar succeeded in proving otherwise through his popular novel, Meniti Rindu (2013). The distinctiveness brought about by Affifudin Omar, particularly concerning issues, sets this work apart from other popular novels. Therefore, this paper aims to analyze the materials used in producing popular novels within Meniti Rindu. It is conducted using textual analysis methods on the novel Meniti Rindu, guided by the framework for producing popular novels introduced by Deborah Hale (1999), consisting of seven materials: characters, conflict, a hook, plot, romance, dark moment, and a happy ending. The study found that Affifudin Omar critically and creatively succeeded in utilizing all seven materials in producing Meniti Rindu. Affifudin Omar departed from the conventions of writing popular novels without discarding its seven main materials. Instead, by addressing issues such as identity, apostasy, and more, he continually distinguishes Meniti Rindu as a significantly different popular novel within the market. This study is essential in showcasing the dynamics of authors’ efforts to uplift popular novels towards improvement